Clinical Effects of Lisdexamfetamine and Mixed Amphetamine Salts Immediate Release in Adult ADHD: Results of a Crossover Design Clinical Trial. Issue 5 (September 2014) - Adler, Lenard A.; Alperin, Samuel; Leon, Terry; Faraone, Stephen
Abstract: Objectives: To examine the clinical effects of equivalent doses of single-blind (SB; patient-blind) lisdexamfetamine (LDX) and mixed amphetamine salts-immediate release (MAS-IR) on adult attention-deficit/hyperactivity disorder (ADHD) in a placebo (PBO)-controlled, crossover design.Methods: Twenty-four subjects were treated sequentially in a fixed order with (1) SB PBO (matching LDX) for 1 week, (2) SB LDX (up to 70 mg/day) for 5 weeks, (3) SB PBO washout for 3 weeks, and (4) open-label treatment MAS-IR (tid up to 45 mg/day) for 5 weeks. Clinical effects on ADHD and executive function were assessed weekly throughout the trial with the ADHD Rating Scale with adult prompts, the Clinical Global Impression Severity Scale (CGI-S), and the Behavior Rating Inventory of Executive Function (BRIEF).Results: Lisdexamfetamine and MAS-IR were generally well tolerated. Significant and equal reductions on ADHD clinician ratings were seen. Significantly greater reductions in CGI-S and selected BRIEF subsets were observed in LDX over MAS-IR treatment. However, in general, baseline scores for MAS-IR treatment did not fully return to the LDX baseline. Adherence in this structured and monitored clinical trial was good for once daily LDX and 3 times a day MAS-IR.Conclusions: In this crossover study, both LDX and MAS-IR had significant effects on ADHD clinician ratings and measures of executive function (with response rates of about 80%); patients in this monitored clinical trial were adherent with once daily LDX and 3 times a day MAS-IR, which may not be the case in real-world clinical practice. The findings of some superiority of LDX over MAS-IR on the CGI-S and BRIEF ratings may be influenced by the variability in the baselines used, but nevertheless should be further investigated in larger scale, parallel-design clinical trials.